2022
DOI: 10.1172/jci146343
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the ASMase/S1P pathway protects from sortilin-evoked vascular damage in hypertension

Abstract: Sortilin has been positively correlated with vascular disorders in humans. No study has yet evaluated the possible direct effect of sortilin on vascular function. We used pharmacological and genetic approaches coupled with study of murine and human samples to unravel the mechanisms recruited by sortilin in the vascular system. Sortilin induced endothelial dysfunction of mesenteric arteries through NADPH oxidase 2 (NOX2) isoform activation, dysfunction that was prevented by knockdown of acid sphingomyelinase ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 70 publications
1
35
1
Order By: Relevance
“…Detailed Methods Figures S1 through S5 Table S1 References [81][82][83][84][85][86][87][88][89][90][91][92][93][94]…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Detailed Methods Figures S1 through S5 Table S1 References [81][82][83][84][85][86][87][88][89][90][91][92][93][94]…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Recently, it was identified that Sortilin/NTSR3 acts as a receptor for the brain lipids carrier Apolipoprotein E (apoE), which confers the most important genetic risk factor for Alzheimer’s disease (AD), demonstrating the involvement of Sortilin/NTSR3 in the neuroprotective action of apoE in AD pathology [ 31 ]. Finally, the role of Sortilin/NTSR3 as a biomarker of risk in cardiovascular disorders in humans has been largely confirmed [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sortilin, a member of the vacuolar protein sorting 10 (VPS10P) family of receptors, has been positively correlated with vascular and metabolic disorders (110). A recent study demonstrated that sortilin induced endothelial dysfunction of mesenteric arteries through NADPH oxidase 2 (NOX2) isoform activation, and the dysfunction could be prevented by knockdown of acid sphingomyelinase (ASMase) or sphingosine kinase 1 (111). Furthermore, plasma ASMase activity and plasma levels of sortilin increased in hypertensive subjects, especially in those with uncontrolled blood pressure (111).…”
Section: Circulating Biomarkersmentioning
confidence: 99%